Spontaneous tension pneumothorax as a complication of Coronavirus disease 2019: Case report and literature review - Fateen Ata (12217764) (2023)
Primary spontaneous tension pneumothorax (STP) is a rare and life-threatening condition. We report a case of COVID-19-pneumonia patient who developed STP as a complication. He had a prolonged hospital stay and was ultimately discharged asymptomatic. A systematic literature search was performed to review studies (N=12) reporting STP in the setting of COVID-19. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.5852